2010
DOI: 10.1007/s11661-010-0443-8
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Videomicroscopy Studies of Eutectic Al-Si Solidification in Al-Si-Cu

Abstract: Al-Si eutectic growth has been studied in-situ for the first time using X-ray video microscopy during directional solidification (DS) in unmodified and Sr-modified Al-Si-Cu alloys. In the unmodified alloys, Si is found to grow predominantly with needle-like tip morphologies, leading a highly irregular progressing eutectic interface with subsequent nucleation and growth of Al from the Si surfaces. In the Sr-modified alloys, the eutectic reaction is strongly suppressed, occurring with low nucleation frequency at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
3
25
1
Order By: Relevance
“…It is clear that modification significantly changes not only the morphology of the eutectic Si particles but also the size of the eutectic cells. As shown in this study and in those by other authors, [14][15][16][17]21] there are distinct changes in the growth modes and, consequently, the porosity formation between unmodified castings and those modified with Na and Sr.…”
Section: A Effect Of Microstructural and Macrostructural Features Onsupporting
confidence: 83%
See 1 more Smart Citation
“…It is clear that modification significantly changes not only the morphology of the eutectic Si particles but also the size of the eutectic cells. As shown in this study and in those by other authors, [14][15][16][17]21] there are distinct changes in the growth modes and, consequently, the porosity formation between unmodified castings and those modified with Na and Sr.…”
Section: A Effect Of Microstructural and Macrostructural Features Onsupporting
confidence: 83%
“…[8] Strontium has been proven to work in a similar fashion to Na, reducing the available number of nuclei for eutectic cells. [13][14][15] However, the effect is different. In Sr-modified alloys, eutectic solidification is preceded by an undercooling of approximately 5 K followed by recalescence and eutectic solidification.…”
mentioning
confidence: 99%
“…This is not the case for Sr-modified eutectic cells. They are large, approximately spherical and well distributed, forming a mushy zone while eutectic solidification takes place [14][15][16][17].…”
Section: / 23mentioning
confidence: 99%
“…Al-Si eutectic cells nucleate in the interdendritic regions (from the surface of Al dendrites in unmodified alloys and independently in modified alloys [10,11,14,15,17]) and then grow into the surrounding intergranular areas, the extent depending on the scale of the eutectic cells. In Figure 1 the eutectic cell boundaries are distinguished by the variation in shade which is a result of variations in the size and shape of the eutectic Si particles, as discussed in Tiedje et al [16] Close to the casting surface the eutectic cells appear to grow in a densely-packed structure (i.e.…”
Section: Dense-packed To Free Growth Transition (Dft)mentioning
confidence: 99%
“…Recent research has shown that changes in the nucleation frequency and macroscopic evolution of the Al-Si eutectic influence the final microstructure and formation of casting defects [3][4][5][6]. Impurity modification, alloy purity, the presence of solute and the solidification conditions are some of the factors that can influence eutectic nucleation, macroscopic growth patterns and the scale and morphology of the microstructure [7][8][9]. However, with the exception perhaps of the modifying elements Sr, Na and Sb, the influence of common alloying elements on eutectic nucleation and the macroscopic evolution of the eutectic phases in Al-Si alloys are relatively unexplored.…”
mentioning
confidence: 99%